ANALISIS PERSEPSI GURU DAN SISWA TERHADAP PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS (MBG) PADA PENINGKATAN FOKUS BELAJAR SISWA DALAM PEMBELAJARAN - Verisa Sadri; Ririn Febriani; Adrias Adrias; Nur Azmi Alwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In Indonesia, the status of education has experienced quite good development, however, in reality, several regions still face various educational problems. The purpose of this study is to describe the implementation of the Free Nutritional Meal Program (MBG) at each level of education, namely elementary, junior high, and senior high, and to analyze its impact on student learning. Unbalanced student nutritional status is one factor that affects the quality of education. This study uses a quantitative approach with a qualitative descriptive research type. Data collection was carried out by distributing questionnaires using Google Form to several respondents at the elementary, junior high, and senior high levels. Poor nutritional conditions significantly impact student concentration, motivation, and activeness during the learning process at school. Therefore, the government launched a Free Nutritional Meal Program (MBG) in an effort to improve health and assist students in the learning process. The focus of this research analysis is aimed at the implementation of the MBG program in schools and the responses of those who experienced this program, which is focused on teachers and students. Previous research has shown that the Free Nutritious Meal Program (MBG) has a positive impact on elementary school students' learning. Based on teacher and student questionnaires, the MBG program helps improve students' concentration, motivation, engagement, and readiness for learning. Students become more focused, less sleepy, more enthusiastic about learning, and more active in classroom activities, creating a more conducive and optimal learning environment.